Midkine is associated with neuroendocrine differentiation in castration‐resistant prostate cancer. Issue 6 (5th November 2012) - Nordin, Anna; Wang, Wanzhong; Welén, Karin; Damber, Jan‐Erik
Abstract BACKGROUND Castration‐resistant prostate cancer (CRPC) is an incurable disease and both androgen‐deprivation therapy (ADT) and neuroendocrine differentiation (NED) are closely related to CRPC transition. More knowledge concerning neuroendocrine (NE)‐transformed PC cells, the NED process and its association with CRPC, is needed. Expression of growth factor midkine (MDK) is correlated with poor clinical outcomes in various human cancers, including PC. In the present study, we have evaluated MDK expression and NED in two separate tumor groups: early and advanced PC. METHODS Immunohistochemical analysis of MDK, the neuronal marker tubulin‐beta III (TUBB3) and the NE‐marker chromogranin A (CGA) in a human archival material consisting of hormone naive (HN)/stage T1b (n = 29) and CRPC (n = 24) tumors. Triple immunofluorescent imaging was performed on a selection of specimens. RESULTS MDK, TUBB3, and CGA were upregulated in CRPC compared to HN tumors. MDK was highly associated to the expression of both CGA and TUBB3, and identified MDK‐positive NE‐like looking cells found to co‐express CGA or, more commonly, CGA together with TUBB3. CGA and TUBB3 staining displayed a partial expression overlap, an overlap almost exclusively displaying also MDK expression. CONCLUSIONS MDK upregulation in CRPC is associated with NED (shown by its relation to CGA and TUBB3). The results suggest that MDK represents an over‐bridging marker between different populations of NE‐like tumor cells, possibly as part of the NED process and associated CRPC transition, something that needs to be evaluated experimentally as does the applicability of MDK as a future target. Prostate 73: 657–667, 2013. © 2012 Wiley Periodicals, Inc.